Summary of the animal homologue section of HLDA8 - Saalmüller, Armin; Lunney, Joan K.; Daubenberger, Claudia; Davis, William; Fischer, Uwe; Göbel, Thomas W.; Griebel, Phil; Hollemweguer, Enoc; Lasco, Todd; Meister, Richard; Schuberth, Hans-Joachim; Sestak, Karol; et al. (Cellular Immunology, 2005)
Development of reagents against leukocyte differentiation antigens in veterinary immunology is slower compared to humans and mice. Cross-reactivity studies with monoclonal antibodies (mAb) generated against human molecules represent an excellent approach for the detection of new reagents for the minor characterised species. Three hundred seventy-seven commercially available mAb from different companies were tested for their reactivity with cells from 17 species—including non-human primates, ruminants, swine, horse, carnivores, rabbit, guinea pig, chicken and fish. In a first round of testing by flow cytometry (FCM) 182 mAb showed reactivity with atleast one of the species described above. Most of the cross-reactivity was found against non-human primate leukocytes, but also species in evolutionarily more distant from humans showed in some cases a clear staining pattern in flow cytometry (FCM). In a second round these FCM-results were confirmed by molecular analyses, by immunoprecipitation studies and analyses on transfectants. Interesting was the broad species-overlapping reactivity of mAb directed against CD9 (11 out of 17 species), CD11a (11/17), CD14 (11/17), CD18 (13/17), CD21 (7/17), CD29 (10/17), CD44 (13/17), CD45 (9/17), CD47 (10/17), and CD49d (13/17), CD61 (6/17), CD86 (7/17), CD91 (5/17), and CD172a (10/17), indicating evolutionary highly conserved epitopes on these surface molecules. Our results suggest the suitability of crossreactive mAb for the animal model studies. Moreover, these findings contribute to our understanding of the evolution of the immune system. Supported by the Veterinary Immunology Committee of IUIS.